2007
DOI: 10.3748/wjg.v13.i2.289
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endoscopic ultrasound-guided fine needle biopsy for diagnosis of pancreatic masses

Abstract: INTRODUCTIONDifferential diagnosis of pancreatic masses is a frequent clinical challenge. Therapeutic decision in this context is mainly based on the ability to establish or exclude malignancy [1] . Although ductal adenocarcinoma is the most frequent cause of pancreatic masses, other neoplasms (e.g. lymphoma, cystic tumours) and benign conditions (e.g. chronic pancreatitis) with different prognoses and treatment options can arise within the pancreas. A histological diagnosis becomes therefore highly relevant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
3
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 34 publications
5
79
3
3
Order By: Relevance
“…A 25-gauge needle is therefore recommended to puncture the head of the pancreas 4 . Several studies have compared the performance characteristics of a 22-gauge needle with those of a 25-gauge FNA needle for sampling pancreatic masses, but most have failed to demonstrate superiority of either needle [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . A recent systematic review and meta-analysis of EUS-FNA for solid pancreatic masses, including a large cohort of patients, revealed that a 25-gauge needle was more sensitive than a 22-gauge needle 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A 25-gauge needle is therefore recommended to puncture the head of the pancreas 4 . Several studies have compared the performance characteristics of a 22-gauge needle with those of a 25-gauge FNA needle for sampling pancreatic masses, but most have failed to demonstrate superiority of either needle [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . A recent systematic review and meta-analysis of EUS-FNA for solid pancreatic masses, including a large cohort of patients, revealed that a 25-gauge needle was more sensitive than a 22-gauge needle 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the specificity of EUS-FNA is close to 100% [24][25][26][27][28] , it has the potential to miss micro-invasion of malignancy into lymph nodes or to give false negative results for a necrotic pancreatic lesion. However, we consider it as representative of daily practice, particularly when it is combined with an adequate clinical and imaging follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Various EUS-guided techniques have been explored to retrieve tissue specimens, including FNA and Tru-Cut needles, with variable success and complication rates (25)(26)(27)(28)(29)(30)(31)(32). of particular interest is the quick-Core ® needle, designed to operate through an echoendoscope.…”
Section: Introductionmentioning
confidence: 99%